2013
DOI: 10.1007/s11011-013-9417-z
|View full text |Cite
|
Sign up to set email alerts
|

Rivastigmine reverses cognitive deficit and acetylcholinesterase activity induced by ketamine in an animal model of schizophrenia

Abstract: Schizophrenia is one of the most disabling mental disorders that affects up to 1 % of the population worldwide. Although the causes of this disorder remain unknown, it has been extensively characterized by a broad range of emotional, ideational and cognitive impairments. Studies indicate that schizophrenia affects neurotransmitters such as dopamine, glutamate and acetylcholine. Recent studies suggest that rivastigmine (an acetylcholinesterase inhibitor) is important to improve the cognitive symptoms of schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…Taken together, our results indicate that the administration of AA prevented the positive symptoms of SZ, and was also able to reduce the activity of AChE observed in the animal model, thereby allowing the possible increase in levels of ACh seen in the synaptic cleft. These results corroborate the findings of Zugno et al (2013). This data shows that Ket induced dysfunction of the cholinergic system in the same ways that have been observed in schizophrenic patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Taken together, our results indicate that the administration of AA prevented the positive symptoms of SZ, and was also able to reduce the activity of AChE observed in the animal model, thereby allowing the possible increase in levels of ACh seen in the synaptic cleft. These results corroborate the findings of Zugno et al (2013). This data shows that Ket induced dysfunction of the cholinergic system in the same ways that have been observed in schizophrenic patients.…”
Section: Discussionsupporting
confidence: 92%
“…In our animals, we observed an increase in the levels of locomotor activity induced by Ket, which was considered an altered behavior related to positive symptoms in an animal model of SZ (Gamma et al 2012, Zugno et al 2013. Krystal et al (1994) also observed similar behavior in humans undergoing subanesthetic doses of Ket.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…MSNs are modulated by both dopamine and acetylcholine (Kreitzer, ), suggesting that the beta oscillation can be upregulated or downregulated, depending on the levels of these two prominent neuromodulators within the striatum. As beta rhythms are involved in cognitive function, it is particularly noteworthy that cognitive function is altered by many of the neuromodulators that affect, directly and/or indirectly, the MSNs of the striatum, including – dopamine (Jaber et al ., ), acetylcholine (Zugno et al ., ), opioids (Iordanova et al ., ), β‐adrenergic agonists (Beversdorf et al ., ), and somatostatin (Tuboly & Vécsei, ).…”
Section: The Mystery Of Multiple Beta Rhythmsmentioning
confidence: 99%
“…Furthermore, NMDAR antagonists including ketamine enhance the activity of acetylcholinesterase, thereby promoting the degradation of acetylcholine and leading to cognitive disorders [64] .…”
Section: The Abnormal Glutamate Receptors Hypothesis and Related New mentioning
confidence: 99%